The Value of Progressive Islamic Education at PRM Wonosari Musi Rawas, South Sumatra - Thoriqul Ikroma, Jarab; Romelah, Romelah; Mardiana, Dina (Annpublisher, 2025)
This research aims to examine the values of Progressive Islamic Education implemented by the Leaders of the Wonosari Muhammadiyah Branch (PRM), Megang Sakti sub-district, Musi Rawas Regency, South Sumatra Province. This research approach is a field study, using qualitative methods. Data collection was carried out through in-depth interviews, observation and documentation. The results of the research show that in its preaching activities, PRM Wonosari is based on tauhid and is based on the Al-Qur'an and As-Sunnah, the values of tajwid and tajwid, the values of rahmatan lil 'alamin, and carrying out renewal. Progressive Islamic Education developed at PRM Wonosari prioritizes the values of wasathiyah (moderation), namely a fair, balanced and inclusive attitude in integrating Islamic teachings with the demands of current developments. These wasathiyah values are realized through an adaptive learning approach, strengthening noble morals and instilling a spirit of openness and tolerance. The implementation of these values is not only reflected in the formal education curriculum but also in inclusive religious and social activities. This research contributes to enriching the concept of Progressive Islamic Education at the local level and shows its relevance in building a society with character and harmony.